2020
DOI: 10.1021/acs.jchemed.9b01101
|View full text |Cite
|
Sign up to set email alerts
|

Community Engagement in Science Through Art (CESTA) Summer Program

Abstract: Despite the importance of chemistry in addressing many of society’s most significant challenges, there is a growing stigma associated with chemicals in our nation, often termed “chemophobia”. We sought to appeal to the public, not only through education, but also through art as an avenue for appreciation with the development of a new one-of-a-kind chemistry-art summer program. In the Community Engagement in Science Through Art (CESTA) summer program, chemistry, sculpture, and engineering students work collabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Phelan et al identified six dimensions of motivation to participate, which were confirmed by factor analysis . As mentioned above, experimentation is often an important part of chemistry outreach events. ,,, Therefore, the authors of this study developed and validated a seventh dimension to reflect a potential focus on research and experimentation. , Individual learning and pursuing interests : This dimension measures the extent to which visitors’ motivation is based on the expectation to learn something new or to follow their existing interests. Social learning : This dimension measures the extent to which the visit is intended to support the learning of a fellow visitor. Social enjoyment : This dimension measures the extent to which the visit is motivated by gaining social experience from the visit. Establishing or enjoying social contacts : This dimension measures the extent to which visitors’ motivation is based on the expectation of creating new social contacts with other people. Relaxation and recuperation : This dimension measures the extent to which visitors’ motivation is based on the expectation of being able to relax and recuperate during the visit. Popularity of the site : This dimension measures the extent to which visitors’ motivation is based on the expectation of visiting a special or even unique place. Research and experimentation: This dimension measures the extent to which motivation to participate is based on the expectation of being able to experiment safely and independently. …”
Section: Theoretical Backgroundmentioning
confidence: 66%
See 2 more Smart Citations
“…Phelan et al identified six dimensions of motivation to participate, which were confirmed by factor analysis . As mentioned above, experimentation is often an important part of chemistry outreach events. ,,, Therefore, the authors of this study developed and validated a seventh dimension to reflect a potential focus on research and experimentation. , Individual learning and pursuing interests : This dimension measures the extent to which visitors’ motivation is based on the expectation to learn something new or to follow their existing interests. Social learning : This dimension measures the extent to which the visit is intended to support the learning of a fellow visitor. Social enjoyment : This dimension measures the extent to which the visit is motivated by gaining social experience from the visit. Establishing or enjoying social contacts : This dimension measures the extent to which visitors’ motivation is based on the expectation of creating new social contacts with other people. Relaxation and recuperation : This dimension measures the extent to which visitors’ motivation is based on the expectation of being able to relax and recuperate during the visit. Popularity of the site : This dimension measures the extent to which visitors’ motivation is based on the expectation of visiting a special or even unique place. Research and experimentation: This dimension measures the extent to which motivation to participate is based on the expectation of being able to experiment safely and independently. …”
Section: Theoretical Backgroundmentioning
confidence: 66%
“…As mentioned above, a variety of scientists and institutions attempt to engage people with and to facilitate learning about chemistry. Several groups and publications foster this through best-practice examples and results from evaluations. ,, ,, However, participation is often analyzed from a retrospective perspective. That is, participants were asked about the event after the event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility to integrate these four scientific disciplines is an opportunity for students to employ the fundamental knowledge of science and mathematics in exploring technology, developing new solutions with an engineering method. A further development of STEM is the inclusion of Arts, giving rise to the STEAM teaching philosophy [39,[58][59][60][61][62], which has the aim to encourage creative solutions, increase motivation and make science learning more attractive.…”
Section: Stem (And Steam) In Chemical Educationmentioning
confidence: 99%
“…Service-learning has become increasingly more prevalent in chemistry curricula. Service-learning is the process where students learn through active involvement in organized service to others . However, the manner in which departments implement service-learning can drastically vary from one program to another. , Herein, we described the use of service-learning as a complement or supplement to the laboratory component of a course with an emphasis on improving college students’ soft skills. The implementation of service-learning utilizing Google Meet allowed college students to actively engage with elementary school students while facilitating their understanding of key chemical concepts and improving their soft skills, regardless of their learning modality, in-person, hybrid, or remote.…”
Section: Introductionmentioning
confidence: 99%